Modification of Traditional Fishing Boat Outriggers into a Simple Electric Power Plant - Nikmatullah, Muhammad Iqbal; Baharuddin, Baharuddin; Zulkifli, Zulkifli; Alwi, Muhammad Rusydi; Sitepu, Andi Husni (Naval Architecture Department, Kalimantan Institut of Technology, 2023)
The outrigger is one of the components of the boat attached to the outside of the boat. Outrigger has a fairly vital function because it can make the boat stable when fishermen do activities at sea. This study aims to determine the potential of electrical energy that can be generated in the outrigger. In this study, the outrigger shape was modified so that the water flow could be directed into the outrigger cylinder and rotate the turbine to produce electrical energy. This modification was carried out without eliminating the main function of the outrigger supporting the stability of fishing boats. The electrical energy produced is stored in the battery to be used as a source of electricity for lighting at night. The results of this study indicate that the electrical energy produced by outriggers can be used as a source of lighting for traditional fishing boats. However, further research is still needed to determine the loss of ship resistance with this modification.